2012
DOI: 10.1097/mpg.0b013e318248ed3f
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Response to Therapy, and Outcome of Gastroparesis in Children

Abstract: Pediatric gastroparesis is a complex condition with variable symptomatology and outcome depending on multiple parameters. Understanding the clinical features and response to therapy will improve our diagnosis and treatment of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
4
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(114 citation statements)
references
References 25 publications
4
98
4
8
Order By: Relevance
“…A recent report characterized gastroparesis as a complication of lung transplantation, particularly in individuals who develop bronchiolitis obliterans [12]. Children may develop gastroparesis from viral infection (18%) or mitochondrial dysfunction (8%) [13]. Affected infants are predominantly boys; most adolescent gastroparetics are girls.…”
Section: Key Pointsmentioning
confidence: 98%
“…A recent report characterized gastroparesis as a complication of lung transplantation, particularly in individuals who develop bronchiolitis obliterans [12]. Children may develop gastroparesis from viral infection (18%) or mitochondrial dysfunction (8%) [13]. Affected infants are predominantly boys; most adolescent gastroparetics are girls.…”
Section: Key Pointsmentioning
confidence: 98%
“… Re (2012) SR (in neonates) (2005) RC, DB, PC—no difference (2003) RC, DB, PC—no difference (2003) RC, DB, vs metoclopramide study (2001) RC, DB, PC—accelerated gastric emptying (2001) P, RC, DB, PC—improved enteral feeding (2001) RC, DB, PC—improved gastric emptying (2001) RC, DB, PC—no difference (2000) RC, DB—no difference (1998) …”
Section: Treatment Optionsmentioning
confidence: 99%
“…Rodriguez et al showed that domperidone administration resulted in 74% of pediatric patients with GP reporting a positive response and 26% reporting complete symptom resolution, the highest rate among prokinetic drugs. In this study, domperidone resulted in less adverse events (6%) when compared to metoclopramide .…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nausea, vomiting, abdominal pain, weight loss and post-prandial fullness are the most common symptoms, and can be treated with dietary modification with a combination of acid suppression therapy, prokinetic and anti-emetic drugs 6 . In the most severe cases, patients require surgical intervention and supplemental nutrition by post-pyloric feeding.…”
Section: Introductionmentioning
confidence: 99%